Lipid/water interface of galactolipid bilayers in different lyotropic liquid-crystalline phases - Hryc, Jakub; Szczelina, Robert; Markiewicz, Michal; Pasenkiewicz-Gierula, Marta (Frontiers in Molecular Biosciences, 2022)
Biophysical studies of biomembranes are carried out on much simpler model membranes, i.e. hydrated lipid bilayers of a controlled lipid composition typical of the specific biomembrane. The lipid/water interface is the most structurally and dynamically complex region of the bilayer. It is because it consists of various chemical groups of the lipids and water molecules; the groups are in constant motion and the interfacial water molecules, even though predominantly bound to the lipids, exchange with bulk water fast. In this study, carried out using computational methods, the organisation of the lipid/water interface of bilayers composed of galactolipids with both α-linolenoyl acyl chains is analysed and compared in three different lyotropic liquid-crystalline phases. These systems include the monogalactosyldiglyceride (MGDG) and digalactosyldiglyceride (DGDG) bilayers in the lamellar phase, the MGDG double bilayer during stalk phase formation and the inverse hexagonal MGDG phase. For each system, lipid-water and direct and water-mediated lipid-lipid interactions between the lipids of one bilayer leaflet and those of two apposing leaflets at the onset of new phase (stalk) formation, are identified. A network of interactions between DGDG molecules and its topological properties are derived and compared to those for the MGDG bilayer.